A Highly Efficient Catalyst for the Suzuki‐Miyaura Cross‐Coupling Reaction of 5‐(5‐chloropyridin‐3‐yl)‐3‐methyl‐1, 3, 4‐oxadiazol‐2(3H)‐one. (22nd August 2018) - Savitha, Bhaskaran; Koti Reddy, Eeda; Parthasarathi, D.; Pakkath, Rajeesh; Sajith, Ayyiliath M.; Ananda kumar, C. S.; Haridas, Karickal R.; Syed Ali Padusha, M.
Abstract : A highly efficient protocol for the synthesis of diverse aryl (heteroaryl) substituted pyridyl oxadiazol‐2(3 H )‐one analogues using Suzuki‐Miyaura cross‐coupling strategy under microwave enhanced conditions is developed. The method is found to be compatible with a wide range of aryl (heteroaryl) boronic acids. Abstract :